2007
DOI: 10.1197/j.aem.2007.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Triage Liaison Physician on Emergency Department Overcrowding and Throughput: A Randomized Controlled Trial

Abstract: A TLP improved important outcomes in an overcrowded ED and could improve delivery of emergency medical care in similar tertiary care EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 21 publications
1
56
2
13
Order By: Relevance
“…[5][6][7] Improved ED triage, bedside registration, physical expansion of hospitals, and regional ambulance programs have been implemented to decrease ED diversion. [8][9][10][11][12] Despite these attempts, ED diversion continues to be prevalent.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Improved ED triage, bedside registration, physical expansion of hospitals, and regional ambulance programs have been implemented to decrease ED diversion. [8][9][10][11][12] Despite these attempts, ED diversion continues to be prevalent.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that having an advanced practitioner or a physician in triage may reduce the ED LOS and rates of leaving without being seen [45,50]. Two randomized trials of physician in triage demonstrated reduced patient LOS by 36 min in one study (12% reduction) [51], and 122 min in the other (35% reduction) [52]. Both of these studies occurred in Canada, however, where delivery care might be diferent than other setings, thus limiting their generalizability [51,52].…”
Section: Improving Emergency Department Patient Throughputmentioning
confidence: 99%
“…16,17 18,19 Although these measures may help reduce patient wait times, it often results in unnecessary tests being ordered. 11,20,21 For economic reasons, it is prudent to limit such requests for unnecessary tests, in turn reducing unnecessary hospital stays and admissions. 6 This study was subject to certain limitations due to its retrospective nature and the method of data collection using patient records.…”
Section: Discussionmentioning
confidence: 99%